Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus pada Sektor Transportasi dan Logisitik yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2021): Studi Kasus pada Sektor transportasi dan Logistik yang terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021 - Fidela Netha Setiani; I Gede Putu Banu Astawa (Vokasi : Jurnal Riset Akuntansi, 2023)
There is a phenomenon of fluctuations that tend to decrease in the stock index of the transportation and logistics sector which is the main factor in research related to company value. This study aims to examine the effect of investment decisions, funding decisions, and profitability partially and simultaneously on company value in the transportation and logistics sector listed on the Indonesia Stock Exchange in 2019 – 2021. This research is a quantitative study using multiple linear regression analysis techniques with the help of SPSS program version 26. The data used in this research is secondary data. The sample is determined by purposive sampling technique or based on certain criteria so as to obtain 51 samples. The results of this study indicate that: (1) investment decisions partially have a positive but not significant effect on firm value, (2) funding decisions partially have a positive and significant effect on firm value, (3) profitability partially has a positive and significant effect on firm value, (4) investment decisions, funding decisions, and profitability simultaneously have a positive and significant effect on firm value.